Overcoming the Five dysfunctions of a team. Mengatasi lima disfungsi sebuah tim - LENCIONI, Patrick (Salemba Empat, 2006)
Overcoming the Five dysfunctions of a team. Mengatasi lima disfungsi sebuah tim